A novel technique for direct reuse of wastewater in combining scouring and bleaching of cotton fabric. Issue 7 (2nd July 2020) - Panda, Sanjay Kumar Bhikari Charan; Mukhopadhyay, Samrat; Sheikh, Javed
Abstract: Wastewater generated from the conventional pretreatment process is having potential to reuse several times for pretreatment of subsequent batches without harming the fabric quality. As the major portion of water is used in textile pretreatment processes, in the present work a novel method was studied for direct reuse of wastewater in combining scouring and bleaching process. The wastewater generated by the conventional pretreatment was reused with and without mixing with freshwater. Simple technique like filtration with nylon mesh was also studied for its effects on efficiency of pretreatment. The pretreated fabrics were characterized using advanced techniques and further evaluated towards efficiency of scouring and bleaching. In order to evaluate the effect of novel pretreatment process involving reuse of wastewater on dyeability, the pretreated fabrics (using both conventional and novel methods) were further studied for dyeability using reactive dyes. The resulting wastewaters were characterized before reuse in novel method. The pretreated fabrics showed insignificant variations in strength and pretreatment efficiency. The dyeability of both fabrics towards reactive dyes was comparable. The volume of effluent generated was greatly reduced in novel method which showed a great promise to save 33% of water in pretreatment process of cotton fabric.